Lived Experiences of 21st Century Teachers in Inclusive Education - Galgao, Christian; Galgo, Jeson; Hibaya, Arthur John; Sotil, Sheba Flourdelise; Doliente, Jocelyn (Journal of Interdisciplinary Perspectives, 2025)
This study explored the lived experiences of 21st-century teachers in inclusive education at San Miguel Technical Vocational School to gain deeper insights into their challenges, strategies, and the meanings they attach to their work during the 2025-2026 school year, providing a basis for implications for practice. It used a qualitative phenomenological design. This study involved 10 participants, selected through purposive sampling, who taught junior and senior high school classes and were interviewed by the researcher using open-ended questions. The data gathered were subjected to thematic analysis. Findings revealed that the participants' lived experiences of the 21st century in inclusive education involved the use of differentiated instruction and collaborative learning. They encountered challenges and successes in navigating inclusive teaching practices: time constraints for differentiated preparation, teacher transformation and growth, and impactful and fulfilling experiences. Moreover, the meanings they associate with their professional roles as inclusive educators in a 21st-century classroom context were ensuring equitable learning opportunities and providing the necessary support for effective inclusive teaching. Teachers often embrace differentiated instruction and collaborative learning to meet the diverse needs of learners, but they frequently struggle with limited time and resources to fully implement these strategies. Despite these problems, the teachers' commitment to providing all students with equal learning opportunities demonstrates their dedication. It highlights the need for more systemic support to maintain inclusive teaching in today's classrooms. Embracing the recommended practices can help ensure the continuous growth of inclusive education, ultimately creating learning environments where every child feels valued, supported, and empowered to succeed.